2000
DOI: 10.1152/ajpheart.2000.279.4.h1864
|View full text |Cite
|
Sign up to set email alerts
|

Protein washdown as a defense mechanism against myocardial edema

Abstract: Myocardial edema occurs in many pathological conditions. We hypothesized that protein washdown at the myocardial microvascular exchange barrier would change the distribution of interstitial proteins from large to small molecules and diminish the effect of washdown on the colloid osmotic pressure (COP) of interstitial fluid and lymph. Dogs were instrumented with coronary sinus balloon-tipped catheters and myocardial lymphatic cannulas to manipulate myocardial lymph flow and to collect lymph. Myocardial venous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Fourth, it was assumed that ⌸ c , ⌸ i , and P out do not change with increasing microvascular pressure. Although ⌸ c would not change with elevated P c , ⌸ i decreases as a result of interstitial protein washdown (40), leading to overestimation of K f . However, recent studies reported that the decrease in ⌸ i with washdown is lower than previously assumed (40).…”
Section: Assumptions Implicit In Gravimetric Techniquesmentioning
confidence: 97%
See 2 more Smart Citations
“…Fourth, it was assumed that ⌸ c , ⌸ i , and P out do not change with increasing microvascular pressure. Although ⌸ c would not change with elevated P c , ⌸ i decreases as a result of interstitial protein washdown (40), leading to overestimation of K f . However, recent studies reported that the decrease in ⌸ i with washdown is lower than previously assumed (40).…”
Section: Assumptions Implicit In Gravimetric Techniquesmentioning
confidence: 97%
“…Although ⌸ c would not change with elevated P c , ⌸ i decreases as a result of interstitial protein washdown (40), leading to overestimation of K f . However, recent studies reported that the decrease in ⌸ i with washdown is lower than previously assumed (40). Thus, when the increase in P c is small (ϳ15 cmH 2 O), the change in ⌸ i may not be significant.…”
Section: Assumptions Implicit In Gravimetric Techniquesmentioning
confidence: 97%
See 1 more Smart Citation
“…Such augmentation is driven by increased flow of interstitial fluid into the lymphatic vessel as a consequence of increased interstitial pressure and an inverse decrease in lymphatic resistance [4,8]. To promote lymph flow, interstitial protein concentration is also diluted in "protein washout" during higher rates of filtration [9], thereby reducing oncotic sequestration of interstitial fluid. Influences such as the phasic contraction of the myocardium and extracardiac thoracic movements further contribute to the dynamic regulation of fluid movement.…”
Section: Lymphatic Functionmentioning
confidence: 99%
“…Hepatic sinusoids, characterized by a fenestrated endothelial lining without a basement membrane, are highly permeable . Because the hepatic interstitial protein concentration is as high as the plasma protein concentration and is unaffected by increases in trans‐sinusoidal fluid flux, “protein washdown” is a relatively unimportant phenomenon in the liver . Therefore, without an appreciable oncotic pressure gradient, increases in sinusoidal hydrostatic pressure lead to a significant increase in the trans‐sinusoidal fluid filtration rate .…”
Section: Introductionmentioning
confidence: 99%